Pendapatan Asli Daerah, Dana Alokasi Umum Dan Dana Alokasi Khusus Terhadap Kinerja Keuangan Pemerintah Kabupaten Gorontalo: Regional Original Revenue, General Allocation Funds and Special Allocation Funds for the Gorontalo Regency Government's Financial Performance - Machmud, Joice; Radjak, Lukfiah Irwan (Universitas Muhammadiyah Sidoarjo, 2018)
This research figures out and analyzes the influence of regency own revenue (PAD), general allocation funds (DAU), and special allocation funds (DAK) on the financial performance of Gorontalo Regency Government, and analyze the dominant variables that affect the Financial Performance of Gorontalo Regency Government. Quantitative approach is applied in this research with multiple regression analysis tools that include Partial Test and simultaneous test. The data used is quantitative internal secondary data, namely LRA period 2012-2016 Gorontalo District Government for all govermental apparatus (SKPD). The results showed that partially, regency own revenue variable (X1) has no significant influence on the value of 0.403 to the financial performance of Gorontalo Regency. General allocation funds variable (X2) has no significant influence with the value of 0.661 on the financial performance of Gorontalo Regency. Special allocation funds (X3) variable has significant influence with significance value 0.000 on financial performance of Gorontalo Regency. It is also shown that simultaneously the independent variables (PAD, DAU and DAK) have a significant effect on the dependent variable, which is the financial performance of Gorontalo Regency Government period 2012-2016 with a significance value of 0.000. It is suggested that further researchers conducting the same study add other variables and use the ratio of local financial independence for performance variables.